Effects of inclination angle and unloading rate of confining pressure on triaxial unloading-induced slip behaviors of shale fractures - Yuan, Zhe; Cao, Yongna; Zhang, Tao; Li, Shuchen; Feng, Xianda (Frontiers in Earth Science, 2025)
The effects of inclination angle θ and unloading rate of confining pressure Uc on the unloading-induced slip behaviors of shale fractures were investigated by conducting triaxial unloading-induced fracture slip experiments. The variations in mechanical stability, frictional behavior, and morphology variation of shale fractures were systematically explored. The results show that with the continuous unloading of confining pressure, the fractures were initiated to slip, then entered the quasi-static slip stage, and eventually entered the dynamic slip stage in sequence. The occurrence of stick-slip events in the quasi-static slip stage was strongly influenced by the θ and Uc. As θ increases from 30° to 50°, the stick-slip events occurred from 0 to 3 times and from 1 to 3 times for Uc = 0.1 MPa/min and 1 MPa/min, respectively. The θ and Uc have a great influence on the interaction mode of the fractures, which directly affects the frictional behavior of the fractures. The slipping failure behavior of the fracture surfaces is mainly controlled by θ, while Uc plays different roles for the samples with different θ. With the increase in θ, the interaction form between asperities during the slip process may be changed into non-tight contact stage. The increase in θ may enhance or weanken the anisotropy of JRC, depending on whether the Uc reached a certain rate between 0.1 MPa/min and 1 MPa/min. Our results may shed light on the seismicity mitigation and safe exploitation of shale gas.